Bibliometric Analysis of Dividend Policy and Stock Market Performance - Judijanto, Loso; Pahrijal, RIval; Muhtadi, Muhamad Ammar (West Science Social and Humanities Studies, 2025)
This study conducts a bibliometric analysis of research on dividend policy and stock market performance using data from Scopus and analytical tools in VOSviewer. The study identifies key research trends, influential authors, and thematic clusters, highlighting the central role of dividend policy in corporate finance. Findings indicate that dividend policy is strongly linked to corporate governance, stock price behavior, and firm valuation, with extensive contributions from the United States and international collaborations. The analysis also reveals regional differences in research priorities, with developed markets focusing on taxation and shareholder wealth maximization, while emerging markets emphasize regulatory challenges and investor protection. Emerging trends suggest a shift toward integrating macroeconomic factors, financial stability, and machine learning techniques in dividend research. This study contributes to the structured understanding of dividend policy’s role in stock market performance and provides a foundation for future research exploring new financial innovations and technological advancements.